Interpreting and operationalizing the incurability requirement in Canada’s assisted dying legislation - Gupta, Mona; Downie, Jocelyn (Frontiers in Psychiatry, 2025)
To access medical assistance in dying (MAiD) in Canada, a person must have a “grievous and irremediable medical condition” defined in part as “a serious and incurable illness, disease, or disability”. Thus, the clinical assessment of the incurability of a person’s condition is central to determining MAiD eligibility. However, the clinical interpretation and operationalization of the term have been uncertain due to the absence of a clear legal definition and evolving legislation. This has led to confusion and controversy in the public and professional discussion of MAiD eligibility. In this paper, we examine various attempts to interpret and operationalize the term “incurable”, identifying the limitations of each approach. We aim to overcome these limitations by proposing a method for operationalizing the term. We argue that our approach: (1) is consistent with the current legal framework, (2) is consistent with the interpretations of the terminology used in the Criminal Code, and (3) reflects the clinical knowledge and reasoning about the full range of medical conditions that can lead to a request for MAiD. In our analysis, we show that incurability cannot be understood only as a feature of a person’s medical condition but resides in the interplay between the nature of the pathology and the person’s treatment decision-making. Our analysis should help with the ongoing operationalization of the incurability requirement in Canada. It may also be helpful to clinicians in other jurisdictions that either invoke or are considering invoking similar terms/concepts.